Confiança, controles e riscos percebidos no âmbito de cadeias de suprimentos - Marconatto, Diego Antonio Bittencourt (2009)
The supply chains have become even more relevant in the current context of business. They integrate themselves through lots of devices, such as trust, one of their basic supporting assumptions. Several authors study the trust as central construct, linked the several other constructs, especially for controls and risks, approached as being intricate. Therefore, this study aimed at answering to the investigated question: how the trust, the controls and the noticed risks influence each other in interorganizational relationships in the extent of a supply chain? This objective was pursued through a multiple case study with qualitative method, operationalized in three removed dyads from a cutting of a national amplitude supply chain. The data collection and its analysis were performed based in the framework by Das and Teng (2001), adapted with variables by Barney and Hansen (1994). Ten theoretical propositions appeared from the results: (1) Pure/strong trust and relational/moral risk are pointed out to the other variables and to the analysis model constructs besides they influence the relational picture in a decisive way; (2) the interpersonal trust generates relevant influences on other variables; (3) the averagestrong trust is the most common type among the several confidence sorts; (4) the efficiency of the controls in the reduction of the noticed risks is mediated by the level of a existent strong/pure trust; (5) the organizations position in a dyad and its power asymmetry are decisive in the definition and implementation of the common controls to those; (6) bargaining power and coercion capacity are efficient elements of control; (7) the internal relationships of the dyads can be influenced by external factors; (8) established relationships among trust, control and risk are contingential; (9) The studied variables exert different influence intensities on each other; and (10) The formative elements of a variable can have plenty of natures and functions. Additionally, the results showed contradictions, confirmations and new elements in the face of the approached theory, allowing the verification that the interrelation among these constructs constitutes a complex phenomenon which escapes the lineal analysis models.